Association of Urinary Incontinence and Body Mass Index with Polycystic Ovary Syndrome - Tayyaba Mustafa Mian, Maryam Mustafa Mian, Sufian Ahmed, Saba Fatima, Wadha Kamran, Nadia Anwer, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Polycystic ovary syndrome (PCOS) is a metabolic disorder, which impacts and effects body's multiple system. Female with more fat deposition in her body and higher body mass index (BMI) will eventually face metabolic disorders like polycystic ovary syndrome, diabetes and urinary incontinence (UI). Muscles in the pelvic floor are susceptible and sensitive to androgen and are easily stimulated by presence or increased levels of androgen and due to hyperandrogenemia muscle mass increases and eventually pressure on Levator Ani and urethral sphincter increases and it causes muscle weakness in the pelvic floor and urinary incontinence and patients often complains with urine leakage. Objective: To describe the association between urinary incontinence and the body mass index with polycystic ovary syndrome. Methodology: The study was analytical cross-sectional study. This study included the sample of 113 nulliparous females having age between 18-45 years. Quota sampling technique was used in this study. Participants were divided into two groups, in one group females with diagnosed PCOS were taken and in other quota we had females without PCOS condition. We provided them the International Incontinence Consultation Questionnaire-Short Form (ICIQ-SF), which is a specific questionnaire that assesses the problem of UI symptoms. Results: ICIQ-SF statistics were checked applying chi-square testing. Results showed value less than Alpha value which was 5% (0.05) so, the results were statistically significant and alternate hypothesis was accepted which showed UI and BMI had a significant relation with PCOS. This study will be beneficial in creating awareness among society that endocrine system and body mass index play important role in causing Urinary Incontinence and other health issues. Conclusion: According to this study's findings, there is a strong correlation between UI and BMI with PCOS. Keywords: Urinary incontinence (UI), Body mass index (BMI), Polycystic ovary syndrome (PCOS), International Consultation on Incontinence Questionnaire-Urinary Incontinence (ICIQ-UI), Pelvic Floor Dysfunction (PFD).